Transitioning Toward Evidence-Based Research in the Health Sciences for the XXI Century - Chiappelli, Francesco (Oxford University Press, 2008)
This article discusses some of the misconceptions of evidence-based research in the health sciences. It proposes that since not all treatments in medicine and dentistry can be evidence-based, clinical applications of the evidence-based process should become a specialty. The case is particularly evident in dentistry. Therefore dentistry is taken in this article as a model for discussion. We propose that to approach dentistry from the viewpoint of the patient-oriented evidence that matters (POEM) is perfectly acceptable so far as we also engage in the process of research evaluation and appraisal in dentistry (READ). We distinguish between dentistry based on the evidence, and evidence-based dentistry. We argue that when invoking an evidence-based approach to dentistry or medicine, it is not sufficient to establish the ‘levels of evidence’, but rather that all evidence-based clinical intervention must undergo the stringent process of evidence-based research so that clinical practice guidelines be revised based on the best available evidence.